Neutrophil Phenotype Correlates With Postoperative Inflammatory Outcomes in Infants Undergoing Cardiopulmonary Bypass. Issue 12 (December 2017) - Huber, Jody N.; Hilkin, Brieanna M.; Hook, Jessica S.; Brophy, Patrick D.; Davenport, Tina L.; Davis, James E.; Colaizy, Tarah T.; Moreland, Jessica G.
Abstract : Objectives: Infants with congenital heart disease frequently require cardiopulmonary bypass, which causes systemic inflammation. The goal of this study was to determine if neutrophil phenotype and activation status predicts the development of inflammatory complications following cardiopulmonary bypass. Design: Prospective cohort study. Setting: Tertiary care PICU with postoperative cardiac care. Patients: Thirty-seven patients 5 days to 10 months old with congenital heart disease requiring cardiopulmonary bypass. Interventions: None. Measurements and Main Results: Laboratory and clinical data collected included length of mechanical ventilation, acute kidney injury, and fluid overload. Neutrophils were isolated from whole blood at three time points surrounding cardiopulmonary bypass. Functional analyses included measurement of cell surface protein expression and nicotinamide adenine dinucleotide phosphate oxidase activity. Of all patients studied, 40.5% displayed priming of nicotinamide adenine dinucleotide phosphate oxidase activity in response to N-formyl-Met-Leu-Phe stimulation 24 hours post cardiopulmonary bypass as compared to pre bypass. Neonates who received steroids prior to bypass demonstrated enhanced priming of nicotinamide adenine dinucleotide phosphate oxidase activity at 48 hours. Patients who displayed priming post cardiopulmonary bypass were 8.8 times more likely to develop severe acute kidney injury as compared to nonprimers. Up-regulation of neutrophil surface CD11b levels pre- to postbypass occurred in 51.4% of patients, but this measure of neutrophil priming was not associated with acute kidney injury. Subsequent analyses of the basal neutrophil phenotype revealed that those with higher basal CD11b expression were significantly less likely to develop acute kidney injury. Conclusions: Neutrophil priming occurs in a subset of infants undergoing cardiopulmonary bypass. Acute kidney injury was more frequent in those patients who displayed priming of nicotinamide adenine dinucleotide phosphate oxidase activity after cardiopulmonary bypass. This pilot study suggests that neutrophil phenotypic signature could be used to predict inflammatory organ dysfunction. Abstract : Supplemental Digital Content is available in the text.